(3Mdd GdebGdI aj TQM fXGFQ GdQSGdIs - (3CHhYHO Gddg eMeO Hf YHO GdQMef GdNWGH GdeGdcjs; (3eMeO Hf CMeO Hf eMeO Hf eMeO Hf Ydj Hf ZGRj GdYKeGfj GdecfGSj , GHf ZGRj , CHh YHO Gddg,J (B919 (3g` s
(3ChdgG (B:s
(3bGd SjOfG GdTjN CHhYHOGddg eMeO Hf YHOGdQMef GdNWGH GdeGdcj GdMeO ddg GdPj LYd UOhQ GdYdeGA NRGFf dLhGgQ GdCMcGe hSjQ dge fXe fXGFQ GdeSGFd s
(3BNQgG (B:s
(3eMQekG Ydjg dCf GdCSHGH dGJDKQ GdfjI GfJgi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B226s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdcj (B412) s
Keywords: (3Gdabg GdeGdcjs